2010
DOI: 10.1111/j.1541-0420.2010.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Liquid Association

Abstract: In 2002, Ker-Chau Li introduced the liquid association measure to characterize three-way interactions between genes, and developed a computationally efficient estimator that can be used to screen gene expression microarray data for such interactions. That study, and others published since then, have established the biological validity of the method, and clearly demonstrated it to be a useful tool for the analysis of genomic data sets. To build on this work, we have sought a parametric family of multivariate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 21 publications
0
64
0
Order By: Relevance
“…In this case, if a genetic marker affects post-transcriptional regulation, its effect may be captured by the change of co-expression patterns of the targets of TFs, so a LA analysis may lead to the identification of such markers, where it may be difficult to detect these signals using single gene expressions as the response. Recently, Ho et al [14] proposed a conditional bi-variate normal model to analyze LA that simultaneously captures means, variances, and correlation between a pair of genes. Under a similar framework, Chen et al [15] proposed a penalized likelihood approach to effectively detecting causal genetic loci using iterative reweighted least squares, and Daye et al [16] further considered the heteroscedastic problem.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, if a genetic marker affects post-transcriptional regulation, its effect may be captured by the change of co-expression patterns of the targets of TFs, so a LA analysis may lead to the identification of such markers, where it may be difficult to detect these signals using single gene expressions as the response. Recently, Ho et al [14] proposed a conditional bi-variate normal model to analyze LA that simultaneously captures means, variances, and correlation between a pair of genes. Under a similar framework, Chen et al [15] proposed a penalized likelihood approach to effectively detecting causal genetic loci using iterative reweighted least squares, and Daye et al [16] further considered the heteroscedastic problem.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the liquid association model was developed to identify mediator genes that can modulate coexpression of other pairs of genes [8]. A few other similar models have been proposed to describe three-way relationships among genes [9-11]. Cancer type dependent coexpression patterns have been reported previously [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these mediator variables can also affect the mean expression levels of these two genes and even their variances. The conditional normal model of Ho et al (2009) allows such a dependency when there is only one mediator variable. When the set of potential mediator variables is large, as in our analysis of the real data sets, we first regressed out the effects of these variables on the mean expressions using regression approaches and then applied our model on the residuals.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has also been applied to analysis of expression quantitative trait loci (eQTL) data in order to identify the genetic variants that can mediate the co‐expression patterns between two genes (Sun, Yuan, and Li, 2008). Ho et al (2009) further extended the LA using a conditional normal model that allows one to characterize means, variances, and liquid association structures. These applications clearly demonstrated that the co‐expression patterns between two genes are often affected by the other genes or variables, which we call dynamic co‐expression in this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation